Larvicidal Activity of Red Betel Leaves (Piper ornatum) Ethanolic Extract Against Mosquito Larvae - Soyata, Amelia; Khoirunnisa, Khoirunnisa; Wahab, Sabda (Sciences of Pharmacy, 2024)
Larvae are the initial carriers of dengue hemorrhagic fever (DHF) and culex, making them significant in disease transmission. Excessive chemical larvicides pose serious risks to human health, thus driving the development of biological alternatives like red betel leaf extract. This study aimed to assess the efficacy of red betel leaf extract in larval control. Using 300 larvae, concentrations of 5%, 6%, and 7% were tested with three replicates over 24 h. The bioassay involved placing the larvae into a plastic container filled with the extract. It was found that ethanol extract from Piper ornatum leaves contained alkaloids, tannins, saponins, flavonoids, and terpenoids. After 24 h, results revealed 83% mortality at 5%, 98% at 6%, and 100% at 7% of extract concentration. Consequently, the 7% concentration showed the fastest efficacy in killing mosquito larvae (100% in 50 min). The LC50 value, representing the concentration at which 50% of larvae are killed, was determined to be 0.04%. Additionally, the LT50 value, indicating the time required to kill 50% of larvae (based on the LC50 value), was found to be 3.34 hours. In conclusion, red betel leaf extract demonstrated promising larvicidal activity against mosquito larvae. Future research is anticipated to prove its safety via in vitro and in vivo test.